Virtuālā izstāde "Fotogrāfiju albums “Prezidiju konventa vīru kora koncertceļojums uz Zviedriju un Norvēģiju”" - Latvijas Universitātes Muzejs (My University, 2018)
Par Latvijas Universitātes Muzeja 2018. gada augusta mēneša priekšmetu tika izvēlēts fotogrāfiju albums “Prezidiju konventa vīru kora koncertceļojums uz Zviedriju un Norvēģiju”. Vairāk par to iespējams uzzināt tam veltītajā virtuālajā izstādē, kurā apskatāmas izteiksmīgākās fotogrāfijas no albuma par Prezidiju konventa vīru kora koncertceļojumu uz Zviedriju un Norvēģiju 1937. gadā.

The photo album “Concert Tour of the Presidium Convention Choir to Sweden and Norway” was chosen as the subject of the month of the Museum of the University of Latvia in August 2018. You can find out more about this in the virtual exhibition dedicated to it, which features the most striking photographs from the album about the Presidium Convention Men's Choir's concert tour to Sweden and Norway in 1937.
Virtual Exhibition "Photo Album "Concert Tour of the Presidium Convention Men's Choir to Sweden and Norway""
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Music; fotogrāfijas; albums; Prezidiju konventa vīru koris; Zviedrija; Norvēģija; koncertceļojums; photos; album; Presidium Convention Men's Choir; Sweden; Norway; concert tour